2013
DOI: 10.4049/jimmunol.1200583
|View full text |Cite
|
Sign up to set email alerts
|

SASH1 Is a Scaffold Molecule in Endothelial TLR4 Signaling

Abstract: Recognition of microbial products by TLRs is critical for mediating innate immune responses to invading pathogens. In this study, we identify a novel scaffold protein in TLR4 signaling called SAM and SH3 domain containing protein 1 (SASH1). Sash1 is expressed across all microvascular beds and functions as a scaffold molecule to independently bind TRAF6, TAK1, IκB kinase α, and IκB kinase β. This interaction fosters ubiquitination of TRAF6 and TAK1 and promotes LPS-induced NF-κB, JNK, and p38 activation, culmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 47 publications
(59 reference statements)
1
51
1
Order By: Relevance
“…SASH1 has been reported to be a regulator of TRAF6 ubiquitination, and a de novo heterozygous variant in TRAF6 has recently been identified in patients with hypohydrotic ectodermal dysplasia. [25][26][27] TRAF6, initially identified as a regulator of NF-κB, also has an important role in tumorigenesis, invasion and metastasis, by modulating various signaling pathways. [28][29][30] Finally, because SASH1 has recently been reported as a scaffold molecule implicated in endothelial TLR4 signaling, which is implicated in innate immune responses, we wondered whether palmoplantar keratoderma and alopecia could be due to chronic fungal infection, but this hypothesis was ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SASH1 has been reported to be a regulator of TRAF6 ubiquitination, and a de novo heterozygous variant in TRAF6 has recently been identified in patients with hypohydrotic ectodermal dysplasia. [25][26][27] TRAF6, initially identified as a regulator of NF-κB, also has an important role in tumorigenesis, invasion and metastasis, by modulating various signaling pathways. [28][29][30] Finally, because SASH1 has recently been reported as a scaffold molecule implicated in endothelial TLR4 signaling, which is implicated in innate immune responses, we wondered whether palmoplantar keratoderma and alopecia could be due to chronic fungal infection, but this hypothesis was ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Finally, because SASH1 has recently been reported as a scaffold molecule implicated in endothelial TLR4 signaling, which is implicated in innate immune responses, we wondered whether palmoplantar keratoderma and alopecia could be due to chronic fungal infection, but this hypothesis was ruled out. 25 Dermatological diseases provide key examples of diseases with variants in the same gene that can either follow autosomaldominant or -recessive inheritance. For instance, anhidrotic ectodermal dysplasia is caused by EDAR and EDARADD variants which produce both recessive loss of function and dominant-negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…34,48,49 Recently, we and others have reported that ECs exposed to EndMT inducers, such as endotoxins and oxidative stress, are able to induce increased endothelial migration similar to that observed in myofibroblasts. [50][51][52] However, the participation of oxidative stress as an inductor of conversion of ECs into myofibroblasts and the underlying mechanism are not known.…”
mentioning
confidence: 99%
“…Both domains can mediate protein-protein interactions (13). However, the SAM domains can serve a more complex function in the way that they mediate protein-protein interactions through homologous and heterologous oligomerization with the SAM regions on other proteins (18). Meanwhile, the SAM domains can mediate binding between Smaug proteins and mRNAs to regulate transcription (13).…”
Section: Discussionmentioning
confidence: 99%
“…The SAM domain mediates protein-protein interactions through homologous and heterologous oligomerization with the SAM domains of other proteins, and it can mediate Smaug protein and mRNA binding to facilitate transcriptional regulation (16,17). SASH1 is a member of a recently described family of SH3/SAM adapter molecules according to its domain structure, thus suggesting a role in signaling pathways (18).…”
Section: Introductionmentioning
confidence: 99%